Current Interpretation of Professional Ethical Requirements to Accountants and Auditors - Natalya D. Brovkina, Marina N. Ermakova, Natalya A. Mislavskaya, Svetlana N. Polenova, Lyudmila V. Sotnikova,; Irina O. Yurasova, Evgeniya E. Lyalkova, (Opción, 2019)
The research objective was to analyze the requirements to professional ethical conduct of accountants. The data analysis stage comprised deduction, induction, and smart modeling that allowed making a connection with psychological knowledge and to critically reconsider the basic concepts of professional ethics of accountants and auditors. As a result, a large majority of the colleagues (96.9%) organizes and maintains accounting records by focusing on the needs and interests of the top management. In conclusion, by honesty the Code means the accountant’s responsibility to act in an open and honest manner in all professional and business relationship.